Smart Investments in the field of innovative entrepreneurship in my concept for economic efficiency and energetic efficiency - Stefan Mehedinteanu, Patrick (International Journal of Scientific Research and Management (IJSRM), 2022)
In my opinion, smart investments in the field of innovative entrepreneurship for economic efficiency and energetic efficiency can be for example free energy devices based on Tesla, Coanda and Faraday ideas(induction generators with prime movers with neodym magnets, Faraday rotors Cages and excited Leyda capacitors) and also based on Atlantis technology free energy devices, Climeworks green chemistry devices,  triboelectric nanogenerators, crystal  devices based on Atlantis technology, Hutchinson effect free energy devices(anticovid 19) in the common aim to obtain economic and energetic efficiency and econometric models of innovation process based on free energy devices. Econometric models used  to demonstrate this type of smart investments can be integrated in Schumpeterian Business Cycles,  Romer Innovation Model, Lucas econometric model, Jan Tinbergen Econometric model for technical progress with trend analysis, Cobb Douglas  and Solow Production Function and  Acs Innovation Growth of the Cities book based also on econometric models mentioned above and other econometric models like Solow Endogenous Growth Model  and also from the book of Henri Bergson, L’evolution creatrice sur site persee.fr collections and with Francois Perroux Les Techniques quantitatives de la planification pour les industries modernes et innovatoires and with Robert Gordon and William Jevons Paradox we can do a visionary econometric model for nowdays for economic efficiency and energetic efficiency  with zero emissions of CO2 by smart investments described as free energy devices.